The Peroxisome-Autophagy Redox Connection: A Double-Edged Sword? - Li, Hongli; Lismont, Celien; Revenco, Iulia; Hussein, Mohamed A. F.; Costa, Cláudio F.; Fransen, Marc (Frontiers in Cell and Developmental Biology, 2021)
Peroxisomes harbor numerous enzymes that can produce or degrade hydrogen peroxide (H2O2). Depending on its local concentration and environment, this oxidant can function as a redox signaling molecule or cause stochastic oxidative damage. Currently, it is well-accepted that dysfunctional peroxisomes are selectively removed by the autophagy-lysosome pathway. This process, known as “pexophagy”, may serve a protective role in curbing peroxisome-derived oxidative stress. Peroxisomes also have the intrinsic ability to mediate and modulate H2O2-driven processes, including (selective) autophagy. However, the molecular mechanisms underlying these phenomena are multifaceted and have only recently begun to receive the attention they deserve. This review provides a comprehensive overview of what is known about the bidirectional relationship between peroxisomal H2O2 metabolism and (selective) autophagy. After introducing the general concepts of (selective) autophagy, we critically examine the emerging roles of H2O2 as one of the key modulators of the lysosome-dependent catabolic program. In addition, we explore possible relationships among peroxisome functioning, cellular H2O2 levels, and autophagic signaling in health and disease. Finally, we highlight the most important challenges that need to be tackled to understand how alterations in peroxisomal H2O2 metabolism contribute to autophagy-related disorders.